Susceptibility of capsicum species and cultivars to ralstonia solanacearum: Anatomical differences and bacterial multiplication in resistant and susceptible cultivars - M. A., Rahman; Abdullah, Hiryati (Universiti Putra Malaysia Press, 1997)
Greenhouse evaluation of 42 accessions/cultivars of Capsicum spp. to bacterial wilt caused by Ralstonia solanacearum revealed that the Malaysian local cultivar 'Kulai' was highly resistant. Three accessions, namely CO 1969, CO 1970 and CO 1553, were moderately resistant; all other accessions were susceptible to highly susceptible. Anatomical study of resistant and susceptible cultivars indicated significant differences in certain anatomical characters. The number of vascular strands per root was fewer, the cortex was thicker, and the length of xylem elements was shorter in the roots of resistant cultivars than the susceptible cultivar. The average number of vascular bundles per plant and the number of xylem elements per vascular bundle were fewer and the length and diameter of xylem elements were shorter in the mid-stem of resistant cultivars. These anatomical characters of resistant plants may contribute to limit or slow down the infection process, movement and multiplication of the pathogen. Multiplication ofR. solanacearum at mid-stem, collar and tap root in stem-inoculated susceptible and resistant chilli cultivars revealed that in susceptible cultivars the bacterial population did not differ at all sites tested, but it differed significantly between cultivars at similar sampling sites. These findings show that the mechanism of resistance to the disease is mainly due to the reduced rate of multiplication of the pathogen within the resistant host.